History of Forest Management in Nepal: An Analysis of Political and Economic Perspective - Ranjit, Yogesh (Economic Journal of Nepal, 2019)
Forest management, a kind of practical application, is technical, scientific and economic principle of forestry to maintain and management. The history of forest management in Nepal is closely associated with the political and economic history of the country. Any change in economic and political and economic situation also directly or indirectly changes the forest management practices of Nepal. The main objective of the study is to analyze the historical development of forest management of Nepal from political and economic perspective. It is a historical and descriptive nature of the study i.e. fully based on the secondary sources of data and information in order to have better understanding about the political and economic effects on forest management practices. The key political changes in the country have been divided into five different periods and thereby notably changes in forest management practices which is starting from the state control and exploitation of forests to people’s participation, protection, and conservation, sustainable, and scientific forest management. People’s participation in forest management has been widely accepted in legal as well as policy level.